Reflexões sobre as pessoas LGBT nas organizações públicas : a diversidade sexual no discurso institucional de uma instituição de ensino federal - Silveira, Thaís Rosário da (2016)
This study aimed to understand the institutional discourse regarding sexual diversity within a federal educational institution. For that, a descriptive, documental and bibliographical research was carried out, with a qualitative approach, in which institutional documents and informative material were collected and analyzed, available on the institution's websites, rectory and campuses. The material obtained was mapped quantitatively in tables, being submitted to a first analysis that allowed gthe classification into categories (pertinent, generic and not pertinent). The pertinent news items were grouped into subcategories, nine of them being chosen to be object of the discourse analysis, in the French line proposed by Michel Pêcheux, focused on the subjectivity of the researcher. In addition, the editions of the Institutional Development Plan were analyzed. In terms of methodological format, the ABNT norms were chosen, highlighting the choice to mention the authors' names in a different way. In the end, it was possible to perceive a mismatch between the proposals contained in these documents and the actions actually carried out and disseminated based on the news published by the institution. In view of this, some measures have been suggested that can be adopted for the equal rights of LGBT people